Innovation and Firm Performance in Indonesian Companies: Is Management Experience Important? - Suwandi Suwandi; Bambang Tjahjadi; Ardiyanto Ardiyanto (AKRUAL: JURNAL AKUNTANSI, 2023)
Innovation is needed to support achieving organizational goals with a satisfactory level of performance. This study aims to analyze the moderating role of corporate managerial Experience, which results in the influence of Innovation on firm performance. The research uses a moderation model, or often a path analysis model tested using SPSS. This study uses 504 samples of companies listed on the Indonesian stock exchange for five years. The study results show that successful managers can be seen from their ability to innovate with creative ideas. Several references indicate that ability can be assessed from seven dimensions: collaboration, environment, finance, knowledge, senior management, risk, and staff.